Protest and Democracy - Arce, Moisés; Rice, Roberta (University of Calgary Press, 2019)
In 2011, political protests sprang up across the world. In the Middle East, Europe, Latin America, the United States unlikely people sparked or led massive protest campaigns from the Arab Spring to Occupy Wall Street. These protests were made up of educated and precariously employed young people who challenged the legitimacy of their political leaders, exposed a failure of representation, and expressed their dissatisfaction with their place in the aftermath of financial and economic crisis. This book interrogates what impacts-if any-this global protest cycle had on politics and policy and shows the sometimes unintended ways it continues to influence contemporary political dynamics throughout the world. Proposing a new framework of analysis that calls attention to the content and claims of protests, their global connections, and the responsiveness of political institutions to protest demands, this is one of the few books that not only asks how protest movements are formed but also provides an in-depth examination of what protest movements can accomplish. With contributions examining the political consequences of protest, the roles of social media and the internet in protest organization, left- and right-wing movements in the United States, Chile's student movements, the Arab Uprisings, and much more this collection is essential reading for all those interested in the power of protest to shape our world.